(untitled) (Research, Society and Development, 2022)
The Bolonha reservoir (Belém, Pará) is eutrophicated and dominated by aquatic macrophytes that are often removed and deposited on the banks of the environment, suffering decomposition. Some microorganisms that live associated with macrophytes return to the environment through leaching, among them cyanobacteria. The objective of the study was to evaluate the growth of the species Anagnostidinema amphibium LBABL-2, in microcosm, by three experiments under different environmental conditions and nutritional stress simulating its growth during the cleaning process of the Bolonha reservoir. Growth was determined by optical density and chlorophyll-a. The species formed a slime mat composed of tangles of green, not capitate, not constricted, not attenuated, slightly curved trichomes 600 μm long, composed of cells that measured, on average, 4.1 μm -2.2 μm in length and width, respectively, and showed cyanophycin granules in the cell wall between two cells. The absence of nutrients was the main stressor of Anagnostidinema amphibium LBABL-2, which showed higher growth in the roots of macrophytes immersed in the reservoir, but low growth in the absence of nutrients. The study will support actions for the management of aquatic macrophytes in the reservoir with emphasis on stressors and growth promoters of cyanobacteria associated with their roots.